2004
DOI: 10.1111/j.0105-1873.2004.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to propolis in 1255 children undergoing patch testing

Abstract: To investigate the frequency and the features of contact sensitization to propolis in children, we patch tested 1255 consecutive children suspected of allergic contact dermatitis with propolis 20% petrolatum over an 8-year period (1995-2002). Positive responses were observed in 5.9% of patch-tested subjects, with a significantly higher frequency in boys than in girls. The dermatitis was localized mainly on the face, hands and limbs. A significant linear increase in the annual frequency of propolis allergy was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 31 publications
3
41
0
5
Order By: Relevance
“…Based on the estimates from this study, 3 of 4 beekeepers with atopic dermatitis were allergic to propolis. According to data in the literature hypersensitivity to propolis in the form of allergic dermatitis more often appears in dermatological patients treated earlier for allergic dermatoses (1.2-6.7%; average 3.82%) [14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the estimates from this study, 3 of 4 beekeepers with atopic dermatitis were allergic to propolis. According to data in the literature hypersensitivity to propolis in the form of allergic dermatitis more often appears in dermatological patients treated earlier for allergic dermatoses (1.2-6.7%; average 3.82%) [14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Beekeepers are more affected by propolis allergy than the healthy population (0.64-1.3%) [14,25,26], but are not more affected by propolis allergy than dermatological patients cured earlier because of allergic dermatoses (1.2-6.7%) [14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the use and popularity of propolis-containing products has been paralleled by the linear increase in the frequency of propolis-related allergic contact dermatitis. Originally, contact allergy to propolis was mostly reported in people with occupational exposure, yet most of the current cases are the result of the use of propolis-containing products that are either applied topically or ingested orally 8 . Ingested propolis has resulted in allergic contact cheilitis, stomatitis, perioral eczema, labial edema, oral pain and dyspnea 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Propolis has been widely used in folk medicine and biopharmacological products for its antiviral, antimicrobial and anti-inflammatory activities. These activities are partially associated with inhibition of prostaglandins and leukotrienes [2,3]. KHAYAAL et al [2] demonstrated that propolis is an effective adjuvant to therapy in asthmatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increased use of propolis in folk medicine and the biocosmetic industry, nonoccupational contact allergy to propolis has risen recently [3]. Sometimes the pollen within the propolis products also plays a role in sensitisation.…”
Section: Discussionmentioning
confidence: 99%